Living in the dark side? Plastic activity in the Bothrops jararaca group (Serpentes, Viperidae) - Banci, Karina R.S. [UNESP]; Eterovic, André; Rosa, Luana G.S.; Marques, Otavio A.V. [UNESP] (De Gruyter, 2025)
The activity of snakes is affected by several ecological factors, being light-dark cycle the most important of them. Bothrops alcatraz and B. jararaca are nocturnal in situ. However, the critically endangered Golden Lancehead, B. insularis, was described as diurnal in Queimada Grande Island, where adults rely mainly on migratory, diurnal birds preyed when they are active. Herein, we present comparative data on the activity of these representatives of the Bothrops jararaca group, testing the following hypotheses: (1) B. alcatraz and B. jararaca are nocturnal even in captivity, and (2) B. insularis is also nocturnal in the absence of birds. Data on the activity of these pitvipers in captivity were obtained using closed circuit television. Daily activity of captive B. insularis was compared to that from the island, where its seasonal pattern was also investigated. Our results show that all three species are intrinsically nocturnal but B. insularis hunts during the day in the wild, being more active in the dry season. We also show that B. jararaca extends its activity through daytime in colder periods. Caudal luring was displayed by all species in captivity, mostly at night in B. alcatraz and B. jararaca, and during the day in B. insularis, even though such differences were not always significant. In summary, we demonstrate that activity may be plastic and influenced by other biotic and abiotic variables apart from the light-dark cycle.
Keywords: Bothrops alcatraz; Bothrops insularis; Bothrops jararaca; daily activity; Golden Lancehead; seasonal activity; snakes